2021
DOI: 10.32074/1591-951x-217
|View full text |Cite
|
Sign up to set email alerts
|

High FOXA1 immunohistochemical expression level associates with mucinous histology, favorable clinico-pathological prognostic parameters and survival advantage in epithelial ovarian cancer

Abstract: Summary Background Forkhead box (FOX) A1 is a potential therapeutic biomarker that has been investigated in various human cancers. Limited data exist about FOXA1 biologic role in epithelial ovarian cancer (EOC). Aim This study assessed FOXA1 immunohistochemical (IHC) expression and evaluated its association with clinico-pathological parameters in EOC including overall and disease-free survivals (OS, DFS) and patient’s outcome. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 31 publications
4
4
0
Order By: Relevance
“…FOX A1 expression was significantly correlated with tumor), bilaterality (P > 0.001), in this work .This results agreed with Elnashar et al (22) , Wang et al (13) , and disagreed with Sheta et al (8) they reported that although there was a propensity for unilateral tumors to express more FOXA1 than bilateral ones, this difference did not achieve statistical significance.…”
Section: G Ssupporting
confidence: 79%
See 4 more Smart Citations
“…FOX A1 expression was significantly correlated with tumor), bilaterality (P > 0.001), in this work .This results agreed with Elnashar et al (22) , Wang et al (13) , and disagreed with Sheta et al (8) they reported that although there was a propensity for unilateral tumors to express more FOXA1 than bilateral ones, this difference did not achieve statistical significance.…”
Section: G Ssupporting
confidence: 79%
“…Regarding tumor metastasis we found lymph node metastasis in (32.6%) of cases , and omental deposits in (32.6%)of cases, this was nearer to that found by Sheta et al (8) . regarding lymph node metastasis (24.5%) , while omental deposits was higher (63.3%) .…”
Section: G Ssupporting
confidence: 74%
See 3 more Smart Citations